Compressive failure mechanism and strength of unidirectional thermoplastic composites based on modified kink band model. (February 2017) - Matsuo, Tsuyoshi; Kageyama, Kazuro
Abstract: A modified kink band model for compressive failure in fiber direction of fiber reinforced composite polymers was investigated and established in this study. Practically modifying the previous kink band model by logically applying a quadratic yield function combining transverse tensile and shear stress to the kinking instability, the modified model was able to determine the compressive strength along with the kink band failure angle theoretically. Especially in case of unidirectional carbon fiber reinforced thermoplastic composites, the compressive test procedure the authors have developed and its results revealed that the kink band failed in out-of-plane direction with each different inclined angle depending on temperature. From the correlation of the observed kink band failure angle and the evaluated compressive strength affected by temperature condition, the modified kink band failure formula was validated.